The synthesis of hexamethylene diisocyanate microcapsules and mechanisms of self-healing geopolymer through an isocyanate- hydroxy system - Yongming Han; Wenting Dai; Yanzhong Ju; Dehong Wang; Mo Liu; Lu Zhou; Xiaolei Zhang; Xue Yang (Case Studies in Construction Materials)
Geopolymer materials represent a promising green cementitious material; however, their relatively poor volume stability and higher risk of cracking limit their engineering applications. Therefore, it is necessary to develop geopolymer concrete with self-healing capabilities. This study uses hexamethylene diisocyanate as the core material and polyethylene wax as the wall material to prepare single-component microcapsules suitable for the highly alkaline environment of self-healing geopolymer concrete through a melt dispersion condensation method. The results show that the microcapsules possess a rough-surfaced spherical core-shell structure and appropriate particle size, offering high mechanical properties and reliable thermal stability. The core content of microcapsules can reach 71.6 % with good sealing performance. The addition of a small amount of microcapsules will improve the mechanical properties of geopolymer and improve the pore size distribution, and the compressive strength reserved rate can be increased by 36.6 %, and the crack repair rate can reach 64.2 %. When isocyanate interacts with hydroxyl groups and water molecules on the matrix surface in the cracked area, variations in microcapsule dosages result in the formation of polyurethane-polyurea bonding materials with diverse structures and types, as well as transition layer bonding with the matrix. The reaction of an appropriate amount of isocyanate with water molecules is beneficial to improving the bonding strength, whereas an excessive reaction weakens it.